Statistical Analysis of the Characteristics and Laws in Larger and Above Gas Explosion Accidents in Chinese Coal Mines from 2010 to 2020 - Huimin Guo; Lianhua Cheng; Shugang Li (Fire)
Gas explosions are the most serious type of accident in coal mines in China. This study analyzed 125 gas explosion accidents that occurred between 2010 and 2020. The results showed that the number of gas explosion accidents and deaths in 2010–2020 was stable and decreasing. The number of larger gas explosion accidents in 2010–2020 is the largest, but the death toll from major accidents was much greater. Coal faces, headings, and roadways are the main locations where gas explosions are initiated. The coal mines in which gas explosions occur in coal faces and headings are mainly “township” enterprises and private mines, all of which engage in illegal operations. The main cause of gas accumulations in roadways is ventilation system failure; these failures can be reduced with improved ventilations system management. The number of gas explosion accidents and related deaths in the Sichuan, Guizhou, and Heilongjiang provinces are very high. The annual change in the frequency of gas explosion accidents, the quarterly distribution of gas explosion accidents, and time during a mining shift when gas explosion accidents occur are closely related to national policies and regulations, company annual production goals, and the mental status of miners, respectively.